THE EFFECT OF FREE TRADE ZONE (FTZ) IMPLEMENTATION IN BATAM, BINTAN AND KARIMUN ISLANDS (BBK) ON TAX REVENUE OF RIAU ISLANDS PROVINCE - Hadi Santoso, Muhammad (FIA UB, 2015)
The Effect Of Free Trade Zone (FTZ) Implementation In Batam, Bintan And Karimun Islands (BBK) On Tax Revenue Of Riau Islands Province. This paper investigates the effect of Free Trade Zone (FTZ) implementation in Batam, Bintan, and Karimun (BBK) Islands tax revenue of Riau Islands Province. Using fixed effect panel data regression analysis, I found that a FTZ in the BBK islands has a positive impact on tax revenue. The impact on tax revenue can be explained through the increase in other kinds of taxes, such as corporate income tax, income tax of article 21 (employment tax), and final income tax. These findings suggest that the implementation of FTZ can be expanded and implemented to other regions in Indonesia by considering each regionâs geographical location, economic potential, and infrastructure.